Penerapan Metode Design Thinking Dalam Pengembangan UI dan UX - Herfandi, Herfandi; Yuliadi, Yuliadi; Zaen, Mohammad Taufan Asri; Hamdani, Fahri; Safira, Azzahrah Maulya (Building of Informatics, Technology and Science (BITS), 2022)
Website is a computer service that is connected with hypertext facilities. A bad user interface that is made carelessly will affect the user experience (UX), so that the information to be conveyed cannot be received properly. The Design Thinking method is proven to be able to provide solutions in designing user interfaces based on the experience, emotions, and situation of the user (user experience). PD. BPR NTB Sumbawa has a website that can be said to have not maximized the function of the user interface and user experience in the manufacturing process. The results of the questionnaire with a Likert scale to 30 respondents resulted in 47% of users agreeing with the inaccurate website layout. Based on these problems, this research applies the Design Thinking method to analyze and develop user interfaces and user experiences. This research resulted in user empathy map, user persona, user interface design based on define, wireframe and prototype stages in responsive form made using Figma. The prototype results have gone through a direct testing process by the user and produced a better display design based on the Design Thinking Method stage. The prototype display design is expected to make it easier for users to use Thinking and increase interaction satisfaction between users and products.